Renqing Changjue alleviates sepsis-induced acute lung injury by regulating renin-angiotensin system and inhibiting inflammatory response - Minxia Zhu; Yaqi Lei; Zhaojun Zhang; Xu Guo; Jing Guo; Ruipeng Wu; Xiaofeng Li; Shibo Tian; Yuanhao Zhao (Immunobiology)
Sepsis, with high morbidity and mortality, represents a systemic inflammatory response syndrome. A common consequence of sepsis is acute lung injury (ALI). Renqing Changjue (RQCJ), a renowned prescription in traditional Tibetan medicine, is reported to have anti-inflammatory effects. The present study was aimed at exploring whether RQCJ could mitigate sepsis-induced ALI and elucidating its underlying mechanism. The rat model of sepsis-induced ALI was established by intraperitoneal injection of lipopolysaccharide (LPS), and high, medium, and low doses of RQCJ were administered. The results indicated that the intervention of RQCJ improved septic symptoms, mitigated the murine sepsis score and pulmonary edema in LPS-induced septic rats, and decreased inflammatory cytokines in lung tissue such as interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and monocyte chemoattractant protein-1 (MCP-1). Furthermore, RQCJ regulated the balance of renin-angiotensin system by enhancing the enzyme activity of angiotensin converting enzyme 2 (ACE2) while inhibiting ACE, thereby promoting the production of angiotensin 1–7 (Ang1–7). This study highlights the multiple protective effects of RQCJ on sepsis-induced ALI, providing a valuable reference for its further development and offering a novel perspective for the treatment of sepsis-induced ALI.